If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 = s + -14 Reorder the terms: 96 = -14 + s Solving 96 = -14 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. 96 + -1s = -14 + s + -1s Combine like terms: s + -1s = 0 96 + -1s = -14 + 0 96 + -1s = -14 Add '-96' to each side of the equation. 96 + -96 + -1s = -14 + -96 Combine like terms: 96 + -96 = 0 0 + -1s = -14 + -96 -1s = -14 + -96 Combine like terms: -14 + -96 = -110 -1s = -110 Divide each side by '-1'. s = 110 Simplifying s = 110
| 9x-5=130 | | -6(a+8)=2a | | 15x-2y=-6 | | -9p+6=-3(3p-2) | | 3=0.2x-7 | | -5(5-2x)+6=3(7x+1) | | 2x+3x+3=4 | | -(5m+7)=-(1-4m)-7m | | 2y-5-(y-3)=17 | | -22-4r=6(3+6r) | | 3(1[3u-3]1)+3(1[2u-4]1)=x | | (4x^5+3x-12)-(3x^3+x-3x-7)= | | 2x-3y-8z+-3x+5y-11z= | | 16+28x-4=180 | | 16+18x-4=180 | | 37x=73 | | 2=-2(1+2)-4(x+5) | | 65x+100=55x-100 | | -28=7(p+3)+3(8p-6) | | 65x+100=55x | | 8x^3-12x^2-6x+9=0 | | 7+8c=7 | | 4x+4y+(-9x)= | | 0=-3x-1+y | | 55x=65x+100 | | 6m+5m-3m=7(m-1) | | 12=-4(1+2n) | | 23.5x+14.75y=739.25 | | 2x+10=7(x-1) | | -3x=6.6 | | 12x-4=-3-(-x) | | 4=-4(3+x) |